ERP SELECTION CRITERIA: THEORETICAL AND PRACTICAL VIEWS - Ratkevičius, Donatas; Ratkevičius, Česlovas; Skyrius, Rimvydas (Ekonomika, 2012)
This article deals with the problems of Enterprise Resource Planning (ERP) system selection as the initial and vital phase of ERP system implementation.Firstly, the paper presents an analysis of different classifications of the fundamental criteria for the ERP system selection process, published in scholar sources, and defines two main groups – software-related, and implementation-related ERP selection criteria. Secondly, combining theoretical and practical approaches, the most significant ERP system selection criteria of both groups are identified and reviewed by analyzing and interpreting their definitions and differences. The study is complemented by adding practical/statistical findings produced by different consultancies.The paper concludes that there is no standard classification of ERP selection criteria. They are classified mostly on the basis of scientists’ research interests.The significance of ERP system functionality as the principal software-related ERP selection criterion is emphasized. Eleven other criteria were defined as important to consider, such as the total costs of the ERP implementation project, vendor reputation, ERP reliability, ease of integration with other systems, technology advance, scalability, upgrading ability, customization / parameterization possibilities; ease of use; flexibility and modularity.The importance of all-round knowledge for a successful ERP implementation is emphasized, including ERP software functionality, project and change management, business processes, organization of training etc. All these areas are closely connected with implementation-related ERP selection factors: organisational fit, end-user readiness, training, system support quality, and the overall ERP implementation success which is predefined by the complexity of business environment as well as the level of business transformation, defined by technological changes.Finally, it is stated that for creating a decision support system which would automate the ERP selection process, the quantitative analysis of ERP selection criteria would be required.